Intensified solar thermochemical CO₂ splitting over iron-based redox materials via perovskite-mediated dealloying-exsolution cycles - Hu, Yue (2022)
Solar thermochemical CO2-splitting (STCS) is a promising solution for solar energy harvesting and storage. However, practical solar fuel production by utilizing earth-abundant iron/iron oxides remains a great challenge because of the formation of passivation layers, resulting in slow reaction kinetics and limited CO2 conversion. Here, we report a novel material consisting of an iron-nickel alloy embedded in a perovskite substrate for intensified CO production via a two-step STCS process. The novel material achieved an unprecedented CO production rate of 381 mL g−1 min−1 with 99% CO2 conversion at 850 °C, outperforming state-of-the-art materials. In situ structural analyses and density functional theory calculations show that the alloy/substrate interface is the main active site for CO2 splitting. Preferential oxidation of the FeNi alloy at the interface (as opposed to forming an FeOx passivation shell encapsulating bare metallic iron) and rapid stabilization of the iron oxide species by the robust perovskite matrix significantly promoted the conversion of CO2 to CO. Facile regeneration of the alloy/perovskite interfaces was realized by isothermal methane reduction with simultaneous production of syngas (H2/CO = 2, syngas yield > 96%). Overall, the novel perovskite-mediated dealloying-exsolution redox system facilitates highly efficient solar fuel production, with a theoretical solar-to-fuel efficiency of up to 58%, in the absence of any heat integration.